Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine the properties of the function \( f(x) = 2\left(\frac{3}{2}\right)^x \) from the given table, let's analyze the data systematically:
The table provided is:
[tex]\[ \begin{array}{|c|c|} \hline x & f(x) \\ \hline 0 & 2 \\ \hline 1 & 3 \\ \hline 2 & 4.5 \\ \hline 3 & 6.75 \\ \hline \end{array} \][/tex]
### Step 1: Check for Constant Additive Rate
First, let's check if the function increases at a constant additive rate. We will look at the differences between consecutive \( y \)-values (\( f(x) \)):
[tex]\[ \begin{aligned} &f(1) - f(0) = 3 - 2 = 1, \\ &f(2) - f(1) = 4.5 - 3 = 1.5, \\ &f(3) - f(2) = 6.75 - 4.5 = 2.25. \end{aligned} \][/tex]
The differences are \( 1 \), \( 1.5 \), and \( 2.25 \), which are not constant. Therefore, the function does not increase at a constant additive rate.
### Step 2: Check for Constant Multiplicative Rate
Next, let's check if the function increases at a constant multiplicative rate. We will look at the ratios between consecutive \( y \)-values:
[tex]\[ \begin{aligned} &\frac{f(1)}{f(0)} = \frac{3}{2} = 1.5, \\ &\frac{f(2)}{f(1)} = \frac{4.5}{3} = 1.5, \\ &\frac{f(3)}{f(2)} = \frac{6.75}{4.5} = 1.5. \end{aligned} \][/tex]
The ratios are all \( 1.5 \), which indicates a constant multiplicative rate. Hence, the function increases at a constant multiplicative rate.
### Step 3: Initial Value
The initial value of the function when \( x = 0 \) is \( f(0) = 2 \), not \( 0 \). Therefore, the statement that the initial value is \( 0 \) is incorrect.
### Step 4: Increment of \( y \)-Values with \( x \)-Values
Finally, let's examine if each \( y \)-value increases by \( 1 \) as each \( x \)-value increases by \( 1 \):
From the differences calculated in Step 1:
- \( f(1) - f(0) = 1 \)
- \( f(2) - f(1) = 1.5 \)
- \( f(3) - f(2) = 2.25 \)
These differences are not equal to \( 1 \). Therefore, the statement that as each \( x \)-value increases by \( 1 \), the \( y \)-values increase by \( 1 \) is incorrect.
### Conclusion:
Among the given statements, the true statement about the function \( f(x) = 2\left(\frac{3}{2}\right)^x \) is that:
The function increases at a constant multiplicative rate.
The table provided is:
[tex]\[ \begin{array}{|c|c|} \hline x & f(x) \\ \hline 0 & 2 \\ \hline 1 & 3 \\ \hline 2 & 4.5 \\ \hline 3 & 6.75 \\ \hline \end{array} \][/tex]
### Step 1: Check for Constant Additive Rate
First, let's check if the function increases at a constant additive rate. We will look at the differences between consecutive \( y \)-values (\( f(x) \)):
[tex]\[ \begin{aligned} &f(1) - f(0) = 3 - 2 = 1, \\ &f(2) - f(1) = 4.5 - 3 = 1.5, \\ &f(3) - f(2) = 6.75 - 4.5 = 2.25. \end{aligned} \][/tex]
The differences are \( 1 \), \( 1.5 \), and \( 2.25 \), which are not constant. Therefore, the function does not increase at a constant additive rate.
### Step 2: Check for Constant Multiplicative Rate
Next, let's check if the function increases at a constant multiplicative rate. We will look at the ratios between consecutive \( y \)-values:
[tex]\[ \begin{aligned} &\frac{f(1)}{f(0)} = \frac{3}{2} = 1.5, \\ &\frac{f(2)}{f(1)} = \frac{4.5}{3} = 1.5, \\ &\frac{f(3)}{f(2)} = \frac{6.75}{4.5} = 1.5. \end{aligned} \][/tex]
The ratios are all \( 1.5 \), which indicates a constant multiplicative rate. Hence, the function increases at a constant multiplicative rate.
### Step 3: Initial Value
The initial value of the function when \( x = 0 \) is \( f(0) = 2 \), not \( 0 \). Therefore, the statement that the initial value is \( 0 \) is incorrect.
### Step 4: Increment of \( y \)-Values with \( x \)-Values
Finally, let's examine if each \( y \)-value increases by \( 1 \) as each \( x \)-value increases by \( 1 \):
From the differences calculated in Step 1:
- \( f(1) - f(0) = 1 \)
- \( f(2) - f(1) = 1.5 \)
- \( f(3) - f(2) = 2.25 \)
These differences are not equal to \( 1 \). Therefore, the statement that as each \( x \)-value increases by \( 1 \), the \( y \)-values increase by \( 1 \) is incorrect.
### Conclusion:
Among the given statements, the true statement about the function \( f(x) = 2\left(\frac{3}{2}\right)^x \) is that:
The function increases at a constant multiplicative rate.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.